Breast Cancer Status in Iran: Statistical Analysis of 3010 Cases between 1998 and 2014 - Mohammad Esmaeil Akbari; Soheila Sayad; Saed Sayad; Maryam Khayamzadeh; Leila Shojaee; Zeynab Shormeji; Mojtaba Amiri (International Journal of Breast Cancer)
Background. Breast cancer is the 5th leading cause of cancer death in Iranian women. This study analyzed 3010 women with breast cancer that had been referred to a cancer research center in Tehran between 1998 and 2014. Methods. In this retrospective study, we analyzed 3010 breast cancer cases with 32 clinical and paraclinical attributes. We checked the data quality rigorously and removed any invalid values or records. The method was data mining (problem definition, data preparation, data exploration, modeling, evaluation, and deployment). However, only the descriptive analyses’ results of the variables are presented in this article. To our knowledge, this is the most comprehensive study on breast cancer status in Iran. Results. A typical Iranian breast cancer patient has been a 40–50-year-old married woman with two children, who has a high school diploma and no history of abortion, smoking, or diabetes. Most patients were estrogen and progesterone receptor positive, human epidermal growth factor (HER) negative, and P53 negative. Most cases were detected in stage 2 with intermediate grade. Conclusion. This study revealed original findings which can be used in national policymaking to find the best early detection method and improve the care quality and breast cancer prevention in Iran.